THE USE OF INNOVATIVE TECHNOLOGIES IN THE TRAINING OF FUTURE CHEMISTRY TEACHERS (World Bulletin of Social Sciences, 2024)
This article provides recommendations on the use of innovative technologies in the system of training future chemistry teachers. Innovative approaches are highlighted as the main factors in the modernization of education
Keywords: innovations; integration; education; pedagogical innovations